THE GUIDELINES FOR ENHANCING KNOWLEDGE AND UNDERSTANDING OF THE SUFFICIENCY ECONOMY PHILOSOPHY AMONG MEMBERS OF THE WOMEN'S DEVELOPMENT FUND, BANG KRUAI DISTRICT, NONTHABURI PROVINCE - มากสุวรรณ, พิชญาภา (Academic Journal Phranakhon Rajabhat University, 2020)
The objectives of this research was to study the knowledge and understanding, compare personal factors with knowledge and understanding and study guidelines for enhancing knowledge and understanding to the Philosophy of Sufficiency Economy of Thai Women Empowerment Fund Members of Bangkruai District, Nonthaburi Province. Phase1, Quantitative Research to study knowledge and understanding and compare personal factors with the knowledge and understanding of the Philosophy of Sufficiency Economy of Thai Women Empowerment Fund Members of Bangkruai District, Nonthaburi Province. The sample was 363 people. The outcome of this research showing that had the overall level of knowledge and understanding of the Philosophy of Sufficiency Economy is on a high level. Once considering in each aspect, The highest level is the knowledge is at a very understandable level, the second is self-immunity-along and the least is the modesty. Compare personal factors shows that differences in age, educational level, occupation and average income per month results in different levels of knowledge and understanding of the Philosophy of Sufficiency Economy, However, marital status do not affect the difference. This difference is at a statistically significant level of 0.05. Phase 2 Qualitative Research, guidelines for enhancing knowledge and understanding to the Philosophy of Sufficiency Economy. The outcome of Focus Group searching guideline for enhancing knowledge and understanding of the Philosophy of Sufficiency Economy of Thai Women Empowerment Fund Members of Bangkruai District, Nonthaburi Province. In all, 5 aspects should have training for knowledge about to the Philosophy of Sufficiency Economy, exchange opinion, and Increased publicity.